PARTICIPATION OF CIVIL SOCIETY INSTITUTIONS IN THE DEVELOPMENT OF THE CULTURE SPHERE - Rodchenko, Larysa; Chervjakova , Olga (Theory and Practice of Public Administration, 2020)
The purpose of the article is the scientific and theoretical justification for determining the participation of civil society institutions in the development of the culture sphere and the strengthening civil society in Ukraine. The methodological basis of work are general scientific and special research methods based on modern scientific principles of state administration, in particular, methods used: identification and comparative analysis - when processing information sources on the subject of research; abstract-logical - for a theoretical generalization, definition of the essence, place and role of civil society institutions in the development of the culture sphere and formulation of conclusions; social diagnostics - to assess the actual state of interaction between public authorities with civil society institutions and other methods of scientific knowledge, which ensured the reliability and objectivity of the study conducted in this article. The scientific novelty of the work consists of systematically formulated and scientifically substantiated theoretical and methodological principles of the participation of civil society institutions in the development of the culture sphere, in particular the role in the life of modern Ukrainian society, their functions, sources of financing, as well as the influence of external and internal factors on their activities. Conclusions. The participation of civil society institutions in the development of the culture sphere involves deideologizing educational and educational activity on the part of the authorities, creation of conditions for peaceful coexistence of different ideologies and styles of civil behavior, which unite, rather than divide the society, the so-called “socio-political consensus”; spread through the educational system, the media culture of knowledge, information about the history, traditions and democratic values ​​of the Ukrainian people; growth and support the national scientific and technical, cultural elite of society, which, on the one hand, shaping the future elite of society, and the second - the most actively involved in public life. And most importantly - the social elite acts carrier democratic political culture.